2008
DOI: 10.1002/chem.200800977
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Evaluation of the pKHBand Δ$H{{{\,\ominus}\hfill \atop {\rm HB}\hfill}}}$ Hydrogen‐Bond Scales of Nitrogen Bases

Abstract: The experimental pKHB hydrogen-bond (HB) basicity scale and the corresponding DeltaH[symbol: see text]HB enthalpic scale of nitrogen compounds are extended and analysed in light of simple theoretical descriptors using the B3LYP density functional method and a medium-size basis set (6-31+G(d,p)).The selected training set includes 59 monofunctional unhindered nitrogen bases for which homogeneous and accurate experimental pKHB and DeltaH[symbol: see text]HB data have been determined by means of the association eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…[18] Hence, the data in Table 1 is limited to the experimental and/or calculated pK BHX values of a few diverse five-membered N-heterocyclic compounds. The basicity range of these compounds appears to be extremely large because the nitrogen atoms belong to very different families depending on the number and positions of the double bonds.…”
Section: Variation Of Hb Acceptor Strength In Five-membered N-heterocmentioning
confidence: 99%
See 3 more Smart Citations
“…[18] Hence, the data in Table 1 is limited to the experimental and/or calculated pK BHX values of a few diverse five-membered N-heterocyclic compounds. The basicity range of these compounds appears to be extremely large because the nitrogen atoms belong to very different families depending on the number and positions of the double bonds.…”
Section: Variation Of Hb Acceptor Strength In Five-membered N-heterocmentioning
confidence: 99%
“…This loss of basicity, in line with the diminution of p character, has been attributed to a reduction of the charge transfer between the nitrogen lone-pair and the anti-bonding XH orbital of the HB donor. [18] The nitrogen basicity of 3-pyrroline (14) is only slightly weakened by the [18] [d] Ref. [24] [e] Ref.…”
Section: Variation Of Hb Acceptor Strength In Five-membered N-heterocmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, theoretical calculations must take into account the flexibility of the monomer to gain a better insight into the structural dependence of the HB basicity. In recent works, [22,67] we have shown that a weighting of the electrostatic potentials or interaction energies by Boltzmann populations provides satisfactory descriptions of the experimental HB basicities.…”
mentioning
confidence: 96%